Multi-factor integrated parametric design of power-split hybrid electric bus. (1st March 2016) - Zeng, Xiaohua; Yang, Nannan; Song, Dafeng; Zhang, Chang; Wang, Junnian; Wang, Jixin; Wang, Qingnian
Abstract: The power-split hybrid electric system is currently the most promising hybrid system. This study proposes a multi-factor integrated parametric design method for a power-split hybrid electric bus (HEB). This method considers the power source efficiency (i.e. the engine, motor and generator), transmission efficiency, vehicle driving cycle requirements, and primary control strategy. The design method is then applied to a specified city bus. System efficiency is analyzed, and the control strategy is determined. Finally, the parametric design method is validated on the co-simulation platform of Matlab/Simulink and Cruise. Results show that the fuel economy of the power-split HEB that adopted the proposed parametric design is 36% better than that of the conventional city bus. Highlights: This paper proposes a parametric design method for power-split hybrid electric bus. The method considers system efficiency, operation requirements and control strategy. The method is applied to conduct the parametric design for a real city bus. Co-simulation results demonstrate the reasonability of the parametric design method.